FIGLEY-MIGLEY’S PROSE: POETICS OF CYNICISM - Irina N. Ivanova (Вестник Северо-Кавказского федерального университета, 2022)
The article is devoted to the analysis of the modern Russian prose development tendencies. The author refers to the literary and socio-cultural context of postmodernism and post-postmodernism. The main idea is that total disappointment in any type of discourse may be quite productive in creative sense and creates specific poetics of intellectual cynicism.